Analisis Pelaksanaan Program Guru Penggerak Pada Pembelajaran Berdiferensiasi Dalam Mewujudkan Mutu Pendidikan Di SMP Negeri 5 Kebumen - Dewanti, Tjandra Agustina; Mulyanto, Mulyanto (Universitas Sarjanawiyata Tamansiswa, 2024)
This study aims to analyze planning, organizing, implementing, monitoring, and evaluating, as well as the effectiveness of Program Guru Penggerak on differentiated learning in improving the quality of education. This type of research uses a qualitative approach method. The research was conducted at SMP Negeri 5 Kebumen, Kebumen District, and Kebumen Regency. Data collection techniques include interviews, observation, and document studies. Data analysis techniques through the stages of data collection, data reduction, data presentation, and data verification. The results of this study indicate that: 1) Planning, organizing, implementing, monitoring, and evaluating the Program Guru Penggerak in differentiated learning is based on the competency of the mobilizing teacher in leading learning that is pro-student in the good category; (2) The teacher-driven program on differentiated learning is effective in realizing the quality of education, which is marked by increased student learning outcomes; the results of supervision of learning by the school principal are in the